Investigation of a highly excited electronic 1Π state of NaLi molecule - Bang, Nguyen Huy; Grochola, Anna; Jastrzębski, Włodzimierz; Kowalczyk, Paweł; Salami, Houssam (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
We report on our investigation of the excitation spectra of the NaLi molecule in the energy range 31000–33900 cm–1. A polarisation labelling technique is used to ensure rotational resolution of the spectra and to enable unambiguous assignment of the NaLi transitions. A hitherto unknown electronic state of 1Π symmetry is observed. Major molecular constants of the state are determined and its potential curve constructed using the inverted perturbation approach method.
Optica Applicata, Vol. 36, 2006, nr 4, s. 499-504
Keywords: optyka; NaLi molecule; laser spectroscopy; electronic states; potential energy curves